Extraterrestial magnetic field effects on attitude determination accuracy of small satellites - Cilden, Demet; Kaymaz, Zerefsan; Hajiyev, Chingiz (IEEE, 2015)
IGRF (International Geomagnetic Reference Field) and Tsyganenko magnetic field models are the selected models for the comparative study. These models can be one of the input vector separately besides the Sun direction to Singular Value Decomposition (SVD) method. Extraterrestrial effects coming from the Sun and/or interplanetary rays are the main consideration for estimating the magnetic field components close to the actual results. Tsyganenko model that uses an index changing with the external effects needs a model (IGRF) simulating the terrestrial magnetic field changes. Proposed models give the results in an acceptable limit with respect to the measurement data. Moreover, Tsyganenko model is the best-fit model if the absolute errors for the attitude angles are calculated. The difference between the defined models can be ignored with decreasing altitude but also become important on the higher orbits.